2009
DOI: 10.1080/00016480802163366
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiotherapy strategies for locally advanced hypopharyngeal cancer after resection and ileocolic flap reconstruction

Abstract: After major surgery, patients treated with IMRT had less toxicity and better functional restoration than those with 2DRT. IMRT and 3DCRT both showed lower dose to the spinal cord than did 2DRT. Only IMRT showed reduced dose to ileocolic flap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Advances in radiation technology have provided better conformal dose distribution to simultaneously hit the target lesions and spare critical organs [9-12]. Nonetheless, areas other than the target area are exposed to significant low dose radiation, making radiation oncologists uncomfortable with this uncertainty in daily practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in radiation technology have provided better conformal dose distribution to simultaneously hit the target lesions and spare critical organs [9-12]. Nonetheless, areas other than the target area are exposed to significant low dose radiation, making radiation oncologists uncomfortable with this uncertainty in daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…These therapies are supposed to produce greater target dose conformity and better critical organ sparing effects, allowing target dose escalation, with lower toxicity to normal tissues [9-12]. Nonetheless, each is usually accompanied by general, low-dose distribution to the torso.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, intensity-modulated radiotherapy (IMRT) has been adopted for reduction of treatment related side-effects in head and neck cancer patients [12-17]. Dosimetry studies have confirmed that IMRT method can deliver more precise dose distribution around the target(s) and maintain lower doses to critical nearby organs [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…With advances in radiotherapy modalities, such as three-dimensional conformal radiotherapy (3DCRT) and IMRT, delivering a good radiation dose to the tumor target volume while sparing the critical organs appears achievable [19,21,22]. With the development of conformal assays, radiation therapy could be an effective choice for selected HCC patients with PVT [20].…”
Section: Introductionmentioning
confidence: 99%